2008
DOI: 10.1007/s11172-008-0139-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of nanocrystalline metal oxides: effect of the real structure and surface chemistry on the sensor properties

Abstract: The relationships between the composition, structure, chemistry of the surface, and sensor properties of nanocomposites SnO 2 -М n О m (M n O m = Fe 2 O 3 , MoO 3 , V 2 O 5 ) obtained by chemical precipitation from solutions were analyzed. The relationships between the elemental and phase composition of the nanocomposites and the effect of the composition on the nanostructure and the acidic and oxidation properties of the nanocomposite surface were considered. The modification of the SnO 2 surface by other oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 65 publications
2
43
0
Order By: Relevance
“…An efficient approach to improve the selectivity of a gas sensing material is the chemical modification of a semiconductor oxide [2,9]. Catalytic additives of noble metals have been established as efficient modifiers, enhancing sensitivity and selectivity to reducing gases, e.g., to CO the efficient modifiers are Pd [10][11][12][13], Au [14,15], Pt [16]; to H2S-CuO [17]; to NH3-RuO2 [18]; to LPG-Pd [19], Au [20].…”
Section: Open Accessmentioning
confidence: 99%
“…An efficient approach to improve the selectivity of a gas sensing material is the chemical modification of a semiconductor oxide [2,9]. Catalytic additives of noble metals have been established as efficient modifiers, enhancing sensitivity and selectivity to reducing gases, e.g., to CO the efficient modifiers are Pd [10][11][12][13], Au [14,15], Pt [16]; to H2S-CuO [17]; to NH3-RuO2 [18]; to LPG-Pd [19], Au [20].…”
Section: Open Accessmentioning
confidence: 99%
“…A promising approach to obtain selective sensor materials is the modification of SnO 2 surface with catalyst in order to create specific centers, which participate in solid -gas interaction. Such centers could act in reactions with gas molecules through formation of surface complexes so the chemical nature of modifier, its red/ox and acid/base properties become decisive factor in sensor response to target molecule [2]. Here we present robust evidence that intrinsic properties of modifiers, such as noble metals and metal oxides (Au, PdO, RuO 2 , NiO, CuO, Fe 2 O 3 , La 2 O 3 , V 2 O 5 , MoO 3 , Sb 2 O 5 ) could be used to obtain sensor material with enhanced sensitivity to particular gas.…”
Section: Introductionmentioning
confidence: 99%
“…Here we present robust evidence that intrinsic properties of modifiers, such as noble metals and metal oxides (Au, PdO, RuO 2 , NiO, CuO, Fe 2 O 3 , La 2 O 3 , V 2 O 5 , MoO 3 , Sb 2 O 5 ) could be used to obtain sensor material with enhanced sensitivity to particular gas. We demonstrate this principle in obtaining sensor materials for detection of typical representatives of different groups of gases, CO, NH 3 , H 2 S, acetone vapor and NO 2 . We postulate that the preliminary analysis of chemical nature of interaction between semiconductor matrix, modification agent and target gas molecule cold be the basis in tailoring of materials for application in the systems for "electronic nose" gas detection principle.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity or selectivity of these reactions is mainly determined by the nature of the available active sites on the surface [41]. Hydroxy groups, chemisorbed oxygen, and coordinatively unsaturated atoms can act as active sites on the oxide surface.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation ability of the oxides is attributed to chemisorbed oxygen and variable valence metal atoms. In the second case, the efficiency of the charge transfer from the matrix to an active cation plays a great role too [41]. Experiment has shown that the use of metal oxide nanocomposites also allows significant increases in the stability of the grain size during annealing, limiting grain growth.…”
Section: Introductionmentioning
confidence: 99%